The Loss of Land Rights under Kasepekang: Balinese Customary Law and Indonesian Agrarian Law - Priyanka Pragas; I Made Wirya Darma (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This study explores the application of kasepekang, the most severe customary sanction in Balinese traditional law, and its implications for land rights over pedruwen desa, particularly Pekarangan Desa (PKD) and Ayahan Desa (ADS). The sanction of kasepekang is imposed on individuals or families who commit serious violations of awig-awig or pararem desa, leading to the loss of their status as members of the customary village (krama desa). This loss of status results in the forfeiture of rights to PKD and ADS lands, which are often inherited and cultivated for generations. Such practices raise complex issues when examined under Indonesia’s national agrarian law, as the Basic Agrarian Law No. 5 of 1960 and Government Regulation No. 24 of 1997 explicitly safeguard long-term land tenure and constitutional rights guaranteed under Article 28H of the 1945 Constitution. The objective of this research is to analyze the concept of kasepekang in Balinese customary law, evaluate its compatibility with national agrarian principles, and formulate a harmonization framework that allows the enforcement of customary sanctions without violating constitutional protections. Employing a normative legal method with statutory, conceptual, and comparative approaches, this study applies Philipus M. Hadjon’s Theory of Legal Protection, Gustav Radbruch’s Theory of Legal Certainty, and John Rawls’ Theory of Justice. The findings confirm that while kasepekang is legitimate within customary law as an instrument of social and religious order, it cannot be extended to revoke PKD and ADS land rights. The novelty of this study emphasizes restricting kasepekang to socio-religious domains, supported by clear mechanisms for mediation and rehabilitation, thereby ensuring legal certainty while preserving the integrity of customary law within the national legal system.